A Systematic Review of Etiology and Treatment for Hyperemesis Gravidarum - Juliana, Mutia; Sianipar, Imelda M.G (International Medical Journal Corp. Ltd, 2024)
Background: Hyperemesis gravidarum (HG) is severe nausea and repeated vomiting that prevents oral intake of food and leads to dehydration, ketoacidosis and nutritional deficiencies that may need hospitalization. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using Medline, Science Direct, Scopus and Embase, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Several pharmaceuticals are currently in use, but there is no evidence regarding which is preferable, when to commence treatment, or what dosage or administration route is most beneficial.